Darline's, Elegant ReTouch open (Raton, NM Raton Range, 1992)
Article is about Darline Baca's business opening.
Newspaper article + Photograph of Darline Baca, Sally Chavez, and Serina Lannon
Master list item #: 11
File location is in the Raton file Cabinet
Keywords: Baca, Darline; Chavez, Sally; Lannon, Serina; Darline's T-Shirt Shop and Elegant ReTouch Boutique; Boutique openings; Business Opening; Local Business; Retail Business; Screen printing; Monogramming; Raton, New Mexico